"How different can we be?": Using Tuesdays with Morrie and intergenerational interactions to promote positive views of older adults among college students. Issue 9 (2nd September 2018) - Atkins, Melissa S.
ABSTRACT: This article reports the results of an Adult Development course assignment. This assignment required that undergraduate students interact with an older adult on two occasions, provide written reflection on these interactions, and read and review the book, Tuesdays with Morrie . The goals of this assignment were for students to comfortably interact with older adults, to recognize the value of intergenerational interactions, and to recognize ageist or stereotyped ideas that they may have held about older adults. The analyses were primarily qualitative, but indicate that these goals were met. Student reactions to this assignment were overwhelmingly positive and insightful. While a number of students expressed initial concern about these interactions, they unanimously reported them to be positive experiences. Students also indicated that it was a learning experience for them, and sometimes for the older adults as well, and several made note of stereotypes or ageist ideas that they had held. Students completed the Fraboni Scale of Ageism after completing these assignments, and scores were significantly below neutral. While pretest, and additional post-test, measures would make the results of this study stronger, the students' reports indicate that they perceived positive change within themselves, which suggests that this was an effective means of promoting positive attitudes about older adults.